"Passageless" Administration of the Nelson–Denny Reading Comprehension Test: Associations With IQ and Reading Skills. (July 2013) - Ready, Rebecca E.; Chaudhry, Maheen F.; Schatz, Kelly C.; Strazzullo, Sarah
There are few tests that assess reading comprehension in adults, but these tests are needed for a comprehensive assessment of reading disorders (RD). The Nelson–Denny Reading Test (NDRT) has a long-passage reading comprehension component that can be used with adolescents and adults. A problem with the NDRT is that reading comprehension test items can be answered correctly without reading the associated passage. The current study determined how IQ, verbal comprehension, and reading skills were associated with scores on a passageless administration of the NDRT. Results indicated that IQ, verbal comprehension, and broad reading skills were significantly associated with greater NDRT passageless scores. Results raise questions about the validity of the reading comprehension component of the NDRT and suggest that the test may have differential validity based on individual differences in vocabulary, general fund of knowledge, and broad reading skills.